Unmasking Racism: Students of Color and Expressions of Racism in Online Spaces. (26th July 2019) - Eschmann, Rob
Abstract: Expressions of racism in the post-Civil Rights Era are expected to be more covert than overt and more unconscious than conscious. But some internet-based communication takes place in technological contexts that are not bound by the same norms as face-to-face interactions, and can structure more explicit presentations of racist ideologies. I explore the changing expressions of racism in online spaces and their effects on students of color using in-depth interviews with 27 undergraduate students of color and their reactions to and interpretations of an online, anonymous student forum. I argue that covert racism is unmasked in online environments, and that exposure to unmasked racial ideologies can challenge students' racial worldviews, adaptive coping responses to racism, relationships to White students and institutions, and dominant racial narratives.